PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN PUBLIK TERHADAP KEBIJAKAN DIVIDEN (STUDI PADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2012-2015 SEKTOR MANUFAKTUR) - Prihartini Rahayu; Makhdalena Makhdalena; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to determine and analyze the effect ofinstitutional ownership and public ownership on dividend policy. The population in thisresearch is all manufacturing companies listed on the Indonesia Stock Exchange for theperiod 2012-2015 that have data institutional ownership, public ownership anddividend policy four consecutive years (2012-2015). Data are obtained from IndonesianCapital Market Directory (ICMD) and website each company. The data analysistechnique used in this research is multiple linear regression with the help of SPSSprogram. The results showed that institutional ownership and public ownershipsimultan eously affect the dividend policy. Partially, institutional ownership negativelyaffect dividend policy and public ownership do not affect the dividend policy.Keywords: Institutional ownership, Public ownership, Dividend Policy